It is time to revise the international Good Clinical Practices guidelines: recommendations from non-commercial North–South collaborative trials. Issue 3 (16th November 2016) - Ravinetto, Raffaella; Tinto, Halidou; Diro, Ermias; Okebe, Joseph; Mahendradhata, Yodi; Rijal, Suman; Gotuzzo, Eduardo; Lutumba, Pascal; Nahum, Alain; De Nys, Katelijne; Casteels, Minne; Boelaert, Marleen
Abstract : The Good Clinical Practices (GCP) codes of the WHO and the International Conference of Harmonization set international standards for clinical research. But critics argue that they were written without consideration for the challenges faced in low and middle income countries (LMICs). Based on our field experience in LMICs, we developed a non-exhaustive set of recommendations for the improvement of GCP. These cover 3 domains: ethical, legal and operational, and 8 specific issues: the double ethical review of 'externally sponsored' trials; the informed consent procedure in minors and in illiterate people; post-trial access to newly-developed products for the trial communities; the role of communities as key research actors; the definition of sponsor; and the guidance for contractual agreements, laboratory quality management systems, and quality assurance of investigational medicinal products. Issues not covered in our analysis include among others biobanking, standard of care, and study designs. The international GCP codes de facto guide national legislators and funding agencies, so the current shortcomings may weaken the regulatory oversight of international research. In addition, activities neglected by GCP are less likely to be implemented or funded. If GCP are meant to serve the interests of global society, a comprehensive revision is needed. The revised guidelines should be strongly rooted in ethics, sensitive to different sociocultural perspectives, and allow consideration for trial-specific and context-specific challenges. This can be only achieved if all stakeholders, including researchers, sponsors, regulators, ethical reviewers and patients' representatives from LMICs, as well as non-commercial researchers and sponsors from affluent countries, are transparently involved in the revision process. We hope that our limited analysis would foster advocacy for a broad and inclusive revision of the international GCP codes, to make them at the same time 'global', 'context centred' and 'patient centred'.